Oncogenic miR-9 is a target of erlotinib in NSCLCs - Chen, Xi (Sci Rep, 2015)
EGFR-targeted cancer therapy is a breakthrough in non-small cell carcinoma. miRNAs have been proved to play important roles in cancer. Currently, for the role of miRNAs in EGFR-targeted cancer therapy is unclear. In this study, first we found that erlotinib reduced the expression of miR-9. MiR-9 expression was increased in human lung cancer tissues compared with peripheral normal tissues, and miR-9 promoted the growth of NSCLC cells. Overexpression of miR-9 decreased the growth inhibitory effect of erlotinib. Second, miR-9 decreased FoxO1 expression by directly inhibition of its mRNA translation. Adenovirus-mediated overexpression of FoxO1 or siRNA-mediated downregulation of FoxO1 negatively regulated cell growth. And exogenous overexpression FoxO1 reduced the pro-growth effect of miR-9. Finally, we found that erlotinib upregulated FoxO1 protein expression. Moreover, overexpression of miR-9 decreased erlotinib-induced FoxO1 expression, and overexpression of FoxO1 enhanced the growth inhibitory effects of erlotinib. Additionally, we found that erlotinib downregulates miR-9 expression through suppressing the transcrption of miR-9-1 and enhanced DNA methylation maybe involved. These findings suggest that oncogenic miR-9 targeted FoxO1 to promote cell growth, and downregulation of this axis was involved in erlotinib’s growth inhibitory effects. Clarifying the regulation of miRNAs by erlotinib may indicate novel strategies for enhancing EGFR-targeted cancer therapy.